Analysis of southern Great Plains ARM cloudiness and surface radiation data - Levy, Robert C., author (Colorado State University. Libraries, 1996)
One scientific question that the ARM (Atmospheric Radiation Measurement) program hopes to answer is, "What are the direct effects of temperature and atmospheric constituents, primarily clouds, water vapor and aerosols on the radiative flow of energy through the atmosphere and across Earth's surface?" (ARM Science Team, 1996). The purpose of this project is to construct a detailed analysis of the clouds over the Central Great Plains (SGP) site and to study their effects on surface radiation. Using data from the October/November 1994 Intense Observation Period at the Central Facility (CF), "composite" daily time series plots have been made, relating cloud levels (cloud base and cloud top), liquid and precipitable water amounts, and the down welling solar and infrared irradiances. From these pictures interesting time periods were selected, such as periods of completely clear skies, nearly uniform single-layer clouds, or multi-layered clouds. For each of these periods, one-hour "averages" or "characteristic values" of CF data were computed to run the CSU GCM (Colorado State University General Circulation Model) radiation parameterization, and modeled flux results were compared with solar and infrared fluxes observed at the CF. Data were grouped into "cloud" and "clear" cases, depending on whether or not a ground-based micro-pulse lidar detected clouds during the one-hour interval. For clear cases, the parameterization needed vertical water vapor, ozone, and carbon dioxide profiles. For cloud cases, additional inputs included cloud fraction and ice/water mixing ratios in cloud layers. The water and ice profiles were obtained using lidar and sounding estimates of cloud base and top (pressure and temperature), along with microwave radiometer estimates of liquid water path and climatological values of cloud ice content. Statistics were used to determine whether the clouds present were one layer or multi-layer. Under clear skies, the resulting modeled down welling solar fluxes were about 10% larger than observed. The longwave fluxes agreed well with observations, although the simulated downwelling longwave was consistently too low, and the simulated outgoing (top of atmosphere) longwave was too high. For one-layer cloudy sky cases, the trends were similar to the clear sky cases. That is, the solar fluxes were calculated higher than observed, the downwelling fluxes were generally modeled too low and the outgoing longwave was generally too high. However, the errors for individual calculations were much larger, likely due to the uncertainty of cloud base and top, the assumptions used in distributing the liquid and ice in the cloud, the values of cloud particle optical parameters used in the model runs, and the simplified physics used in the parameterization itself.
December 1996.
Also issued as author's thesis (M.S.) -- Colorado State University, 1996.
Keywords: Atmospheric radiation -- Great Plains --Measurement; Clouds -- Great Plains